Hermansky Pudlak Syndrome and Pulmonary Alveolar Proteinosis at the same patient: first case report in the world literature - Ozyilmaz, Ezgi; Gunasti, S.; Kuyuku, Y.; Kuleci, S.; Hanta, I.; Kocabas, A. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Hermansky-Pudlak Syndrome (HPS) is a rare autosomal recessive disorder presenting with oculocutaneous albinism, bleeding diathesis and lysosomal accumulation of ceroid lipofuscin which leads to interstitial fibrosis in lung. Pulmonary fibrosis which is usually associated with HPS-1 and HPS-4 subtypes usually manifests in the third/fourth decades of life representing with giant lamellar bodies of alveolar type-II-cells and their apparent degeneration causes restrictive lung disease. Pulmonary manifestation of this syndrome may lead to premature death. Pulmonary Alveolar Proteinosis(PAP) is another rare disease characterized by alveolar deposition of surfactant phospholipids and proteins secondary to defective clearance by alveolar macrophages. PAP may occur as autoimmune diseases and/or secondary to toxic inhalation, systemic infections or hematological disorders. None of the cases were reported secondary to HPS according to the best our knowledge. As well, pulmonary involvement of HPS was never reported as PAP. We report the first case of PAP in a patient with HPS.